Optimizing Laptop Charging Efficiency with the MPPT Algorithm in a Fast Charging System for USB-C PD (Power Delivery) Based Laptops - Christian Putra Simanungkalit; Solly Aryza; Beni Satria (SEAN Institute, 2026)
The rapid advancement of portable electronic device technology, particularly laptops, necessitates a charging solution that is faster, more efficient, and compatible with diverse standards. The USB-C Power Delivery (USB-C PD) protocol has emerged as a universal charging standard due to its ability to support flexible voltage and current configurations. Nevertheless, the overall charging efficiency remains constrained by dynamic load behaviour, fluctuations in power sources, and the limitations of conventional power management techniques. This paper described the integration of a Maximum Power Point Tracking (MPPT) algorithm into a USB-C PD-based fast-charging system for laptops, aiming to enhance energy transfer efficiency between the power source and the device. The research methodology involves the design and simulation of a power management system incorporating MPPT, hardware prototyping, and performance evaluation based on efficiency, charging duration, and voltage stability metrics. Experimental results indicate that the implementation of the MPPT algorithm significantly improves charging efficiency, minimizes energy losses, and reduces charging time compared to conventional charging methods. The proposed approach not only contributes to the advancement of USB-C PD-based fast-charge technologies but also lays a foundation for future developments in intelligent, energy-efficient power management systems. These findings have broad potential applications in next-generation electronic devices that demand fast, adaptive, and sustainable charging solutions.